LUNG NEOPLASIA: PATHOPHYSIOLOGY - Cabral Barbosa, Alice; de Oliveira Arantes, Arthur; de Almeida Sousa, Jéssica; Carolina Rios Fonseca, Maria; Mitsue de Castro Matsuoka, Sarah (Health and Society, 2022)
The objective of this article is to explore the main aspects that define lung neoplasms with emphasis on their pathophysiology, their epidemiological profile and their clinical management since diagnosis, available treatments and means of prevention based on a review of scientific literature.